2010
DOI: 10.30843/nzpp.2010.63.6568
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the European earwig <i>Forficula auricularia</i> to insecticide residues on apple leaves

Abstract: The European earwig (Forficula auricularia) is potentially a predator of a number of insect pests in apple orchards However its effectiveness as a natural enemy in apple orchards may be compromised by insecticide sprays A laboratory bioassay of eight insecticides currently used in Integrated Fruit Production (IFP) apple orchards and one asyet unregistered product was undertaken to determine their effects on earwigs Adult earwigs were placed in ventilated containers where they were exposed to insecticide residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 10 publications
(8 reference statements)
1
24
0
1
Order By: Relevance
“…In spring, nymphs of the third instar migrate from the soil to the tree motivated by the increase of the temperature (Gobin et al 2008) which can explain the decrease of the abundance on soil. F. auricularia is an omnivorous species, feeding on a high variety of food items such as softfleshed fruit and plant material as well as a wide range of arthropods (Shaw and Wallis 2010), and is referred as an important generalist predator (Gobin et al 2008). In Crete, Neuenschwander et al (1983) observed F. aetolica Brunner predating B. oleae pupae in laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In spring, nymphs of the third instar migrate from the soil to the tree motivated by the increase of the temperature (Gobin et al 2008) which can explain the decrease of the abundance on soil. F. auricularia is an omnivorous species, feeding on a high variety of food items such as softfleshed fruit and plant material as well as a wide range of arthropods (Shaw and Wallis 2010), and is referred as an important generalist predator (Gobin et al 2008). In Crete, Neuenschwander et al (1983) observed F. aetolica Brunner predating B. oleae pupae in laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Although effects on mobility were not always directly studied, spinosad side effects on this trait were observed for the predators C. carnea, 60 D. brevis, 66 Doru luteipes (Scudder) 119 and F. auricularia 70 and for the parasitoids Eiphosoma vitticolle Cresson 34 and H. didymator. 110,111 This effect is mostly due to direct intoxication by the pesticide, which results in a knockdown effect, trembling and lack of coordination in legs, wings, mandibles and palpus.…”
Section: Sublethal Effects 321 Physiological and Behavioural Subletmentioning
confidence: 99%
“…Adult coccinellids are also mobile, but they can also fly out of the orchard, avoiding toxic exposure. In addition, most studies have probed no lethal effect of chlorantraniliprole regarding adult predators (Preetha et al 2010;Shaw and Wallis 2010;Campos et al 2011;Gradish et al 2011). Novaluron is a chitin synthesis inhibitor, and it only affects immature stages (Cutler and Scott-Dupree 2007;Trostanetsky and Kostyukovsky 2008).…”
Section: Discussionmentioning
confidence: 99%